APPLICATION OF DEMONSTRATION STRATEGY AND COMPUTER AIDED INSTRUCTION ON STUDENTS' ACQUISITION OF KEYBOARDING SKILLS: A REVIEW OF ITS EFFECTS - Ademiluyi, Lawrence Fem; Olupayimo, Esther Olaitan (Journal of Education and Practice, 2022)
Purpose: The advent of information and communication technology has brought to the front burner the need for students and teachers alike to master the craft of keyboarding. This study investigates the effects of demonstration strategy and computer aided instruction on students' acquisition of keyboarding skills in colleges of education in South-west, Nigeria. Methodology: Quasi experimental research was adopted for the study. Specifically, the pre-test, post-test non-equivalent control group design was used. The population consisted of 1,729 NCE one business education students in 11 public colleges of education in South-west, Nigeria. The sample size comprised 620 NCE one students out of which 582 (94%) participated fully in the study. Simple random sampling technique was adopted and intact classes were used as experimental and control groups. The instrument for data collection was Keyboarding Skill Acquisition Test (KSAT) developed by the researcher and validated by four experts. The reliability of the instrument was determined using Spearman Rank Order Correlation which yielded a coefficient of 0.80. The instrument was administered as pre-test to both experimental and control groups. The treatment was applied for six weeks after which the post-test was administered. Mean and standard deviation were used in answering the research questions while Analysis of Covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. The results were presented in tables. Findings: Findings revealed that teaching with computer aided instruction (mean = 53.69, SD = 9.47) had a significant higher positive effect on students' acquisition of keyboarding skills than demonstration strategy (mean = 47.87, SD = 11.04) and lecture strategy (mean = 40.78, SD = 12.56). Unique contribution to theory, practice and policy: Teaching with demonstration strategy and computer aided instruction have salutary effect on students' acquisition of keyboarding skills but computer aided instruction is more effective in the teaching and learning of keyboarding and similar business education skills than other strategies. Therefore, business educators should always endeavour to teach keyboarding with computer aided instruction to improve students' learning outcome in tertiary institutions.